Exploring the Modulatory Effects of Gut Microbiota in Anti-Cancer Therapy - Li, Wenyu; Deng, Xiaorong; Chen, Tingtao (Frontiers in Oncology, 2021)
In the recent decade, gut microbiota has received growing interest due to its role in human health and disease. On the one hand, by utilizing the signaling pathways of the host and interacting with the immune system, the gut microbiota is able to maintain the homeostasis in human body. On the other hand, the abnormal microbiota composition could also contribute to the generation of several pathogenic conditions including diabetes, obesity, psychiatric disorders and gastrointestinal diseases. More importantly, by producing bacterial toxins, reactive oxygen species (ROS) and immunosurveillance inhibitors, this altered microbiota profile may further lead to oncogenesis and tumor progression. Recent insights have especially focused on the important role of gut microbiota in current anticancer therapies, including chemotherapy, radiotherapy, immunotherapy and surgery. Research findings have indicated a bidirectional interplay between gut microbiota and these therapeutic methods, in which the implementation of different therapeutic methods could lead to different alterations in gut microbiota, and the presence of gut microbiota could in turn contribute to different therapeutic responses. As a result, manipulating the gut microbiota to reduce the therapy-induced toxicity may provide an adjuvant therapy to achieve a better therapeutic outcome. Given the complex role of gut microbiota in cancer treatment, this review summarizes the interactions between gut microbiota and anticancer therapies, and demonstrates the current strategies for reshaping gut microbiota community, aiming to provide possibilities for finding an alternative approach to lower the damage and improve the efficacy of cancer therapy.